Bacterial catabolism of lignin‐derived aromatics: New findings in a recent decade: Update on bacterial lignin catabolism. Issue 6 (28th November 2017) - Kamimura, Naofumi; Takahashi, Kenji; Mori, Kosuke; Araki, Takuma; Fujita, Masaya; Higuchi, Yudai; Masai, Eiji
Summary: Lignin is the most abundant phenolic polymer; thus, its decomposition by microorganisms is fundamental to carbon cycling on earth. Lignin breakdown is initiated by depolymerization catalysed by extracellular oxidoreductases secreted by white‐rot basidiomycetous fungi. On the other hand, bacteria play a predominant role in the mineralization of lignin‐derived heterogeneous low‐molecular‐weight aromatic compounds. The outline of bacterial catabolic pathways for lignin‐derived bi‐ and monoaryls are typically composed of the following sequential steps: (i) funnelling of a wide variety of lignin‐derived aromatics into vanillate and syringate, (ii) O demethylation of vanillate and syringate to form catecholic derivatives and (iii) aromatic ring‐cleavage of the catecholic derivatives to produce tricarboxylic acid cycle intermediates. Knowledge regarding bacterial catabolic systems for lignin‐derived aromatic compounds is not only important for understanding the terrestrial carbon cycle but also valuable for promoting the shift to a low‐carbon economy via biological lignin valorisation. This review summarizes recent progress in bacterial catabolic systems for lignin‐derived aromatic compounds, including newly identified catabolic pathways and genes for decomposition of lignin‐derived biaryls, transcriptional regulation and substrate uptake systems. Recent omics approaches on catabolism of lignin‐derived aromatic compounds are also described.